2012
DOI: 10.1016/j.atherosclerosis.2012.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytochrome P450-derived eicosanoids in humans with stable atherosclerotic cardiovascular disease

Abstract: Objective Preclinical and genetic epidemiologic studies suggest that modulating cytochrome P450 (CYP)-mediated arachidonic acid metabolism may have therapeutic utility in the management of coronary artery disease (CAD). However, predictors of inter-individual variation in CYP-derived eicosanoid metabolites in CAD patients have not been evaluated to date. Therefore, the primary objective was to identify clinical factors that influence CYP epoxygenase, soluble epoxide hydrolase (sEH), and CYP ω-hydroxylase metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 30 publications
4
87
0
1
Order By: Relevance
“…We recently reported that obesity was associated with signifi cantly lower circulating EET levels in humans with established cardiovascular disease ( 26 ). Although prior studies have demonstrated that experimental induction of obesity reduces EETs in liver, kidney, and mesenteric arteries ( 21,31 ), as well as alters cyclooxygenase-mediated prostaglandin biosynthesis and lipoxygenase-mediated leukotriene biosynthesis in adipose tissue ( 32,33 ), the impact of obesity on EET bioavailability in adipose tissue has not been rigorously investigated .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that obesity was associated with signifi cantly lower circulating EET levels in humans with established cardiovascular disease ( 26 ). Although prior studies have demonstrated that experimental induction of obesity reduces EETs in liver, kidney, and mesenteric arteries ( 21,31 ), as well as alters cyclooxygenase-mediated prostaglandin biosynthesis and lipoxygenase-mediated leukotriene biosynthesis in adipose tissue ( 32,33 ), the impact of obesity on EET bioavailability in adipose tissue has not been rigorously investigated .…”
Section: Discussionmentioning
confidence: 99%
“…The residue was reconstituted in 30% ethanol, and EET and DHET concentrations were quantifi ed by HPLC-MS/MS. The 14,15-EET:14,15-DHET ratio was calculated as a biomarker of sEH metabolic activity ( 26 ).…”
Section: Cyp Epoxygenase and Seh Activity Assaymentioning
confidence: 99%
“…[26][27][28] The hyperpolarization of smooth muscles and vasodilation induced by EETs are mediated by activation of Ca 2+ -dependent K + channels, with stronger cardioprotection leading to activation of K(ATP) channels. 29) Considering that EET concentrations and the 14,15-EET/14,15-DHET ratio in plasma have negative correlations with the risk of cardiovascular events, 30,31) a decrease of the EETs concentration in patients taking ARBs would correlate with an increase risk of cardiovascular events including sudden cardiac death and myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant oxylipid signaling has been shown to lead to a number of pathologies important to cardiovascular disease including hyperlipidemia, hypertension, thrombosis, and hemostasis 13. For example, coronary artery disease patients have higher plasma levels of CYP‐mediated AA metabolites (namely, the oxylipids epoxyeicosatrienoic acid) 14. While some studies have described the effects of aspirin on individual oxylipids,15, 16, 17 to our knowledge, the systematic effect of aspirin on oxylipid as a class has not been described.…”
Section: Introductionmentioning
confidence: 99%